Hyperthyroidism Secondary to Disseminated Mucormycosis in a Child with Acute Lymphoblastic Leukemia: Case Report and a Review of Published Reports - Irga, Ninela (Springer Netherlands, 2012)
Thyroiditis due to fungal infection is an extremely rare cause of hyperthyroidism. The most common etiological factor of thyroiditis is Aspergillus. Infections due to members of the Mucorales have been an increasing clinical problem in recent years, and the prognosis in generalized infections due to those fungi is usually very poor. No hyperthyroidism in a child with thyroiditis due to mucormycosis has been reported in the literature so far. We describe a clinical course of generalized mucormycosis with thyroid involvement in a 12-year-old girl treated for acute lymphoblastic leukemia. The child underwent a hyperthyroidism connected with thyroid involvement due to a fungal process. The diagnosis was based on the clinical signs, laboratory findings and typical ultrasound scan; however, later attempt to amplify the fungi DNA from the tissue block has failed. The child died because of multiorgan failure due to general fungal infection 49 days after the invasive fungal infection was diagnosed. The generalized mucormycosis is always connected with poor prognosis and the mortality is high.